Peran Taman Bacaan Masyarakat berbasis inklusi sosial dalam mendukung tercapainya tujuan pembangunan berkelanjutan di Kabupaten Bandung - Elnovani Lusiana; Andri Yanto; Samson CMS (Berkala Ilmu Perpustakaan dan Informasi, 2023)
Introduction Libraries with a variety of resources and information services can support the Sustainable Development Goals (SDGs) in society. This study describes the role of social inclusion-based TBM in Bandung Regency, West Java to support SDGs. Data collection methods. This study was qualitative with a descriptive approach. Data analysis was started with data reduction, data display and conclusion. Results and Discussion. TBM contributes to build a community-based literacy ecosystem based on the community characteristics and information needs in their environment. Literacy activities at TBM may improve individual or group skills and give impacts to the community's quality of life through collborations with multiple parties. TBM is a place for consultation regarding life problems in the community by providing access to information and knowledge to support the community's productivity and welfare. Conclusion and suggestions. The presence of community-based TBM supports poverty alleviation efforts. Literacy programs at TBM can help improve people's life skills by giving them more empowerment, training, and mentoring. These activities have an impact on improving individual abilities and skills. TBM becomes a bridge for public libraries as information service providers and a place to find information to overcome life's problems.